ANTIOXIDANT ACTIVITY IN NYPA FRUITS (Nypa fruticans) WITH DIFFERENT LEVELS OF RIPENESS - Ikhsanul Khairi; Anhar Rozi; Afdhal Fuadi; Akbardiansyah Akbardiansyah; Muhammad Arif Nasution; Heriansyah Heriansyah; Fazril Saputra (Universitas Teuku Umar, 2022)
Antioxidants play role in increasing the resistance of the human body, including from virus attacks and weather changes. Antioxidants are found in fruit and are influenced by secondary metabolites formed in the fruit. Along with the level of fruit ripeness, will affect the composition of secondary metabolites, thus affecting antioxidant activity. This study aims to determine the yield and ripeness level of Nypa fruit with high antioxidant activity. The yield of old nipa fruit pulp is higher than young nipa fruit pulp, 15.26% and 9.82% respectively, The antioxidant activity of old Nypa palm juice is in the high category, with an IC50 value of 59.2 ppm and the antioxidant activity of young Nypa palm fruit is in the medium category with an IC50 value of 48 ppm. Antioxidants in old Nypa fruit are better than in young Nypa fruit